VARIASI VIRULENSI VIRUS TUNGRO BERSUMBER DARI INOKULUM DI DAERAH ENDEMIS TUNGRO DI INDONESIA - Nyoman Widiarta; Syahrir Pakki (Universitas Lampung, 2015)
Variations in virulence of tungro viruses from various inoculum sources in tungro endemic areas in Indonesia. Rice tungro disease is caused by virus which is effectively transferred by the green leafhopper. Reactions of resistant varieties to virus sources of inocula from 15 tungro endemic areas were employed as indicator of variations of virus virulence. The green leafhopper of Sukamandiâ€™s population was used as the vector and allowed to transfer viruses Â acquired from tungroâ€™s infected plants from 15 tungro endemic areas to five groups of virus resistant varieties based on parent source of resistance using free choice screening box method. The results showed that the most resistant variety was group V1-Tukad Petanu, followed by V4-Tukad Unda, V2-Tukad Balian and V3-Bondoyudo. Based on resistance test result group variety of V1-Tukad Petanu is recommended for 15 provinces source of incula except for Sulawesi Utara. Group variety of V4-Tukad Unda is not recommended to plant in Yogyakarta and Banten provinces. Group V2-Tukad Balian is not recommended to plant in Bali, Sulawesi Utara, Banten and Kalimantan Selatan provinces. Group V3-Bondoyudo is not recommended to plant in Jawa Tengah, Yogyakarta, and Banten provinces. There were variations in virus virulence among sources of inocula. Six virulence variants were identified, i.e. 001 (Jawa Barat, Nusa Tenggara Barat, Sulawesi Selatan, Jawa Timur, Lampung, Sulawesi Barat, Sulawesi Tengah, Sulawesi Tenggara, Papua), 011 (Jawa Tengah), 021 (Bali, Kalimantan Selatan), 051 (Yogyakarta), 071 (Banten) and 121 (Sulawesi Utara).